Synthesis and Characterization of FeÐ†Ð† , CoÐ†Ð† , NiÐ†Ð† , CuÐ†Ð† and ZnÐ†Ð† Complexes With Dithiocarbamate and N-Donor Ligands - Mohammed, Mohammed Jassim; Ali, Asmaa Basim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New complexes of first series of transition metals with P-amino benzene dithiocarbamate of the general formula [M(PABdtc)2] and [ M(PABdtc)2(L)n] M=Fe( Ð†Ð† ),Co( Ð†Ð† ),Ni( Ð†Ð† ) ,Cu(Ð†Ð†) and Zn (Ð†Ð†). PABdtc = Paraamino benzene dithiocarbamate ,n=2 when L= Py,É£-Pic,iso qunoline ,3,5lutidine n=1when L=1,10-phenanthroline, en, 2,-2bipy.and the type(R)4N[Ni(PABdtc)3] R= methyl, ethyl are prepared. Physico chemical characterization of these complexes was applied using magnetic susceptibility measurements, molar conductance , Infrared and electronic spectra, Metal content measurements, molar conductance indicate complexes of the type [M(PABdtc)2] and [M(PABdtc)2(L)n] are non-electrolyte while complexes of the type (R)4N[Ni(PABdtc)3] are 1:1 electrolyte. Magnetic moment and electronic spectra indicate that the complexes of the type [M(PABdtc)2] are tetrahedral geometry while the complexes of the type [M(PABdtc)2(L)n] and (R)4N[Ni(PABdtc)3] have octahedral geometry